#### Answer

The equation of the stretched graph is $$y=3\sqrt{x+1}$$

#### Work Step by Step

For $c\gt1$, the graph is scaled:
- $y=cf(x)$ - stretched - vertically - factor of $c$
- $y =\frac{1}{c}f(x)$ - compressed - vertically - factor of $c$
- $y=f(cx)$ - compressed - horizontally - factor of $c$
- $y=f(\frac{x}{c})$ - stretched - horizontally - factor of $c$
$$y=\sqrt{x+1}$$
The graph is STRETCHED - VERTICALLY - by a factor of $3$.
Therefore, the equation of the new graph is $$y=3\sqrt{x+1}$$